(untitled) (Research, Society and Development, 2022)
The educational process has undergone changes that accompany society and this implies changes in the attitude of both the teacher and the student. While the student needs to develop different skills to adapt himself to the new reality, the teacher needs to find ways that allow him to understand the content and prepare for the job market. From this perspective, this work aims to present a possibility for the pharmacist to act, in an experimental and interdisciplinary way, using active methodology (project-based learning) for a group of students from the senior year of high school in the city of Toledo, Paraná. In the experiment, the students were proposed to develop a solid pharmaceutical form (chocolate pills). It was observed that the chosen methodology allowed the development of skills and attitudes, since the students had the opportunity to improve their synthesis ability, the transformation of theoretical knowledge into experiential knowledge, the use of adequate vocabulary, teamwork and critical thinking. As a result, it is noteworthy that the methodology used provoked the enchantment of the students, who were all the time engaged in the activities, from the initial period of the discussion to the practical execution of the proposed activity.